Mickey Mouse Clubhouse (Bath : Parragon, 2015)
"Join Mickey Mouse and all his Clubhouse pals as they take to the skies in a hot-air balloon! But when their balloon gets stuck, they end up lost and far from home. Who will save the day?"--Cover.
At head of title: Disney.
Keywords: Children's stories